La inclusión educativa y su incidencia en el proceso de enseñanza - aprendizaje de los niños y niñas de segundo y tercer grado del nivel de formación de educación general básica de la escuela “Juan Ramón Jiménez”, de la parroquia Casanga, cantón Paltas, provincia de Loja, período 2012 – 2013” lineamientos propositivos - Suárez Rivas, Olga Miranda (2014)
This research refers to : EDUCATION INCLUSION AND RELIANCE ON THE LEARNING PROCESS OF CHILDREN OF SECOND AND THIRD GRADE LEVEL OF GENERAL EDUCATION BASIC TRAINING SCHOOL "JUAN RAMON JIMENEZ", DE LA CASANGA, AVOCADO CANTON, LOJA PROVINCE , PERIOD 2012 PARISH - 2013" PROPOSITIONAL GUIDELINES , for which worked with the General Objective: To determine if teachers give importance to Inclusive Education as a means of linking and fair share of the teaching - learning in students of 2nd to 3rd Grade General Education Basic of "Juan Ramón Jiménez" School. The methods, techniques and procedures used in the research process to test hypotheses were the method : empirical , inductive and to study the results the analytical method was applied, the technique used was the survey of teachers, students, mothers and parents of "Juan Ramón Jiménez" School which enabled verify hypothesis. The field research was developed with a total of 9 teachers, 70 parents and 72 students of the Second and Third Degree of General Basic Education "Juan Ramón Jiménez" School. After applying the tools and analyze data concluded that: Teachers School "Juan Ramón Jiménez" are aware of the implementation of inclusive education in the educational system, so do not exclude any student; There is good student-teacher thus facilitating the teaching - learning relationship; parents also rely on the skills of your children's teachers and that teachers apply appropriate strategies to maintain the school organization. As recommended Plan workshops for school retreats, to strengthen relationships within the institution, this will benefit the students and to help them become more aware of what is happening within the context in which they develop; That the faculty hold positive attitude and offer support to people with disabilities.